Implementasi Pendidikan Karakter Berbasis Core Value: Studi Fenomenologi Budaya Sekolah di SD Nasima - Lulu’ Arifatun Munasiroh; Wasino; Tri Astuti; Arghita Aricindy (Jurnal Ilmiah Literasi Indonesia, 2025)
This study explores the implementation of character education based on core values as the foundation for school culture development at SD Nasima Semarang. Using a qualitative phenomenological approach, data were collected through in-depth interviews, participant observation, and document analysis involving principals, teachers, students, and parents. The implementation of the school’s core values—strong integrity, readiness to take responsibility, empathy, confidence in striving for the best, and communicative courtesy—has been systematically internalized through daily routines, teacher role modeling, and school regulations to cultivate a culture characterized by moral integrity, religious values, and global competitiveness. Effective school management supported by collaborative leadership and parental engagement sustains this culture, while continuous character reinforcement programs address challenges such as inconsistent teacher modeling and digital influence. The study concludes that SD Nasima has developed a living value system that harmonizes Islamic spirituality, Pancasila values, and global citizenship competencies, offering a replicable model for elementary schools in Indonesia